Criteria for Classification of S.L.E. Issue 5871 (14th July 1973) - Davis, P.; Atkins, Brenda; Josse, R. G.; Hughes, G. R. V.
Abstract : Of 38 patients with systemic lupus erythematosus (S.L.E.) followed in this clinic during the past two years raised levels of anti-DNA antibodies were found in 36. The recently proposed criteria for the classification of S.L.E. were met in 33 of these 36 patients. Three patients with raised DNA antibody titres and some of the features of S.L.E. did not meet the criteria for a classification of S.L.E.